'A world where nothing is solved': Investigating the Anthropocene in True Detective. Issue 2 (1st October 2017) - Coley, Rob
In the HBO series True Detective (2014–present), the material world is no mere backdrop. It is not a neutral geography against which the theatre of human drama takes place, nor does it simply take the form of a psychological landscape, understood as an expression of the interior terrain of the show's protagonists. This particular crime drama does not rely on the stabilizing dualism of exterior/interior, nor does it concern itself with an interaction between these apparently separate realms. Instead, True Detective deals with the consequences of living as part of a world in which such dualisms – and the humanist assumptions upon which they are based – are subject to mass extinction, a world in which a long-held belief in the separability of culture and nature, of free will and determinism, of the organic and the technological, is no longer tenable. Here, far from peripheral to practices of detection and investigation, the material world is an active agent inseparably entangled in such practices. In this article I contend that True Detective maps present trauma concerning a geohistorical period scientists have designated the Anthropocene, and, in doing so, radically exploits a crisis in the anthropocentric conventions of the genre.